Disaster risk analysis of technological failure of industrial estate: a case study: - Rachmawati, Turniningtyas Ayu; Rahmawati, Dwi (Jurnal Sistem dan Manajemen Industri, 2023)
The world has agreed on reducing disaster risks through Sendai Framework for Disaster Risk Reduction (SFDRR) 2015–2030. Efforts to reduce disaster risks are one way to attain Sustainable Development Goals related to "sustainable cities and communities." The first points of disaster risk reduction priorities inscribed in the SFDRR 2015–2030 incorporate disaster risk studies. While studies on natural disaster risks have been widely conducted, non-natural (manmade) disaster risk studies are relatively scant, particularly for technological failure disasters. In this paper, the author investigates the levels of technological failure disaster risks in Gresik Regency, Indonesia, one of the National Strategic Areas in East Java Province. This study employs a disaster risk analysis encompassing aspects of hazard and vulnerability through map overlays with the help of a Geographical Information System (GIS) to identify areas with risks of technological failure. Results illustrate that a high risk is predominantly spread in areas with high hazards, which is 60 m radius of the industrial area. The findings in this study may help shed light on the hazards that may arise due to technological failures that span not only around the source of hazard, i.e., the industrial areas, but also beyond them, and also conclude that the higher the disaster risk is, the higher the vulnerability of an area will be.